High-strength plastic material for anchor bolt and plastic anchor bolt

By using high-strength plastic materials with modified basalt fibers and specific modifiers, the problem of poor durability of plastic anchor bolts in low temperature environments is solved, and high tensile bearing capacity and stability under low temperature conditions are achieved.

CN119331412BActive Publication Date: 2025-03-21MEIJIANLI HANDAN HARDWARE MFG PLANT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411875804.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Plastic anchor bolts have poor durability in low temperature environments, resulting in a decrease in mechanical strength and affecting the fixing effect.

Method used

High-strength plastic materials including polyamide resin, modified basalt fibers and specific modifiers are used to modify the basalt fibers through titanate coupling agent and silicon-containing compound to improve the low temperature resistance of plastic anchors.

Benefits of technology

The tensile bearing capacity of plastic anchor bolts in low temperature environments is significantly improved, ensuring their fixation effect and stability under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of plastic anchor bolts, and proposes a high-strength plastic material for anchor bolts and a plastic anchor bolt. The high-strength plastic material for anchor bolts comprises the following raw materials in parts by weight: 50-60 parts of polyamide resin, 30-40 parts of polypropylene, 10-20 parts of modified basalt fiber, 0.6-1 part of compatibilizer, and 1-2 parts of lubricant. The modified basalt fiber is obtained by modifying basalt fiber with a modifier, and the modifier comprises a titanate coupling agent and a silicon-oxygen-containing compound. Through the above technical scheme, the problem of poor low-temperature resistance of plastic anchor bolts in the related art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic anchor bolts, and in particular to a high-strength plastic material for anchor bolts and a plastic anchor bolt. Background Art

[0002] In the field of traditional mechanical connections, metal anchors have always dominated. Metal anchors have the advantages of high strength, good electrical conductivity and thermal conductivity, and can meet the strict requirements for fastening connections in many industrial scenarios. They are widely used in many industries such as automobile manufacturing, aerospace, and mechanical equipment, and play a key role in building stable mechanical structures and ensuring close fit between components. However, with the continuous advancement of science and technology and the increasing diversification of application scenarios in various industries, metal anchors have also exposed some limitations. First, metal anchors are prone to rust and corrosion, which weakens the mechanical properties of the anchors; secondly, the thermal conductivity of metal anchors will become an unfavorable factor in certain application scenarios. For example, in the external insulation system of the exterior wall of a building with thermal insulation requirements, the thermal conductivity of the metal anchor will destroy the thermal insulation effect of the insulation layer, form a thermal bridge, and increase energy consumption. In the external insulation system of the exterior wall of a building, plastic anchors can reliably fix the insulation board to the wall without destroying the thermal insulation performance of the insulation board. However, plastic anchor bolts have poor low-temperature resistance. When exposed to low-temperature environments for a long time, the mechanical strength of the plastic anchor bolts decreases, affecting the fixing effect. Therefore, how to improve the low-temperature resistance of plastic anchor bolts is a problem that needs to be solved at present. Summary of the invention

[0003] The present invention provides a high-strength plastic material for an anchor bolt and a plastic anchor bolt, which solves the problem of poor low-temperature resistance of the plastic anchor bolt in the related art.

[0004] The technical solution of the present invention is as follows:

[0005] The present invention provides a high-strength plastic material for an anchor bolt, comprising the following raw materials in parts by weight: 50-60 parts of a polyamide resin, 30-40 parts of a polypropylene, 10-20 parts of modified basalt fibers, 0.6-1 parts of a compatibilizer, and 1-2 parts of a lubricant. The modified basalt fibers are obtained by modifying basalt fibers with a modifier, and the modifier comprises a titanate coupling agent and a silicon-oxygen-containing compound.

[0006] As a further technical solution, the amount of the modifier added is 1% to 3% of the mass of the basalt fiber.

[0007] As a further technical solution, the mass ratio of the titanate coupling agent to the silicon-oxygen-containing compound is 7:3-5.

[0008] In the present invention, the mass ratio of the titanate coupling agent to the silicon-oxygen-containing compound is limited to 7:3-5, thereby further improving the low temperature resistance of the plastic anchor bolt.

[0009] As a further technical solution, the mass ratio of the titanate coupling agent to the silicon-oxygen-containing compound is 7:4.

[0010] In the present invention, the low temperature resistance of the plastic anchor is further improved by limiting the mass ratio of the titanate coupling agent to the silicon-oxygen-containing compound to 7:4.

[0011] As a further technical solution, the titanate coupling agent includes one or both of isopropyl tri(dioctyl pyrophosphate) titanate and isopropyl tri(isostearoyl) titanate.

[0012] As a further technical solution, the silicon-oxygen-containing compound includes one or more of 1,3-bis(3-carboxypropyl)tetramethyldisilane, tri(vinyldimethylsilyloxy)methylsilane, and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane.

[0013] As a further technical solution, the silicon-oxygen-containing compound is 1,3-bis(3-carboxypropyl)tetramethyldisilane.

[0014] In the present invention, the low temperature resistance of the plastic anchor is further improved by limiting the silicon-oxygen-containing compound to 1,3-bis(3-carboxypropyl)tetramethyldisilane.

[0015] As a further technical solution, the method for preparing the modified basalt fiber comprises the following steps:

[0016] The basalt fiber is added into a solvent, a modifier is added for modification, and the modified basalt fiber is obtained after drying.

[0017] As a further technical solution, the solvent is deionized water.

[0018] As a further technical solution, the modification temperature is 50-60° C., and the modification time is 2-3 hours.

[0019] As a further technical solution, the compatibilizer includes one or two of maleic anhydride grafted polypropylene and polyethyleneimine.

[0020] As a further technical solution, when the compatibilizer includes maleic anhydride grafted polypropylene and polyethyleneimine, the mass ratio of the maleic anhydride grafted polypropylene to the polyethyleneimine is 5:1-3.

[0021] In the present invention, the mass ratio of maleic anhydride grafted polypropylene to polyethyleneimine is limited to 5:1-3, thereby further improving the low temperature resistance of the plastic anchor bolt.

[0022] As a further technical solution, the lubricant includes one or more of N,N'-ethylene bisstearamide, calcium stearate, and erucamide.

[0023] The present invention further provides a plastic anchor bolt, comprising a screw and a plastic expansion tube with a disc, wherein the material of the plastic expansion tube with a disc is the high-strength plastic material for the anchor bolt.

[0024] As a further technical solution, the method for preparing the plastic expansion tube with a disc comprises the following steps:

[0025] The anchor bolt is mixed with a raw material of a high-strength plastic material and then extruded to obtain a plastic expansion tube with a disc.

[0026] The working principle and beneficial effects of the present invention are:

[0027] The present invention proposes a high-strength plastic material for anchor bolts. The low-temperature resistance of polyamide resin is utilized. The polyamide resin is used as a base material, and basalt fibers modified by titanate coupling agents and silicon-containing compounds are added to further improve the low-temperature resistance of the plastic material for anchor bolts. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following embodiments and comparative examples:

[0030] Polyamide resin, model: PA66 79G13HSL; polypropylene, model: HJ730L; polyethyleneimine, weight average molecular weight: 10000; maleic anhydride grafted polypropylene, model: Exxelor PO 1020; basalt fiber, diameter of 3~8μm, length of 1mm.

[0031] Example 1

[0032] A method for preparing a plastic expansion tube with a disc for a plastic anchor bolt comprises the following steps:

[0033] 50 parts of polyamide resin, 30 parts of polypropylene, 10 parts of modified basalt fiber, 0.6 parts of maleic anhydride grafted polypropylene, and 1 part of calcium stearate are mixed, and then extruded to obtain a plastic expansion tube with a disc for a plastic anchor bolt;

[0034] The preparation method of modified basalt fiber comprises the following steps: adding 66 g of basalt fiber into 500 mL of deionized water for dispersion, adding 0.66 g of a modifier for mixing, heating to 50° C., continuously stirring for 3 hours, and obtaining the modified basalt fiber after drying; the modifier is composed of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane in a mass ratio of 7:1.

[0035] Example 2

[0036] A method for preparing a plastic expansion tube with a disc for a plastic anchor bolt comprises the following steps:

[0037] 55 parts of polyamide resin, 35 parts of polypropylene, 15 parts of modified basalt fiber, 0.8 parts of maleic anhydride grafted polypropylene, and 1 part of N,N'-ethylene bisstearamide are mixed, and then extruded to obtain a plastic expansion tube with a disc for a plastic anchor bolt;

[0038] The preparation method of modified basalt fiber comprises the following steps: adding 66 g of basalt fiber into 500 mL of deionized water for dispersion, adding 1.32 g of a modifier for mixing, heating to 50° C., continuously stirring for 3 hours, and obtaining the modified basalt fiber after drying; the modifier is composed of isopropyl tri(isostearoyl) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane in a mass ratio of 7:1.

[0039] Example 3

[0040] A method for preparing a plastic expansion tube with a disc for a plastic anchor bolt comprises the following steps:

[0041] 60 parts of polyamide resin, 40 parts of polypropylene, 20 parts of modified basalt fiber, 1 part of maleic anhydride grafted polypropylene, and 2 parts of erucic acid amide are mixed, and then extruded to obtain a plastic expansion tube with a disc for a plastic anchor bolt;

[0042] The preparation method of modified basalt fiber comprises the following steps: adding 66 g of basalt fiber into 500 mL of deionized water for dispersion, adding 1.98 g of a modifier for mixing, heating to 60° C., continuously stirring for 2 hours, and obtaining the modified basalt fiber after drying; the modifier is composed of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane in a mass ratio of 7:1.

[0043] Example 4

[0044] The only difference between this embodiment and embodiment 1 is that the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 1:1.

[0045] Example 5

[0046] The only difference between this embodiment and embodiment 1 is that the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 7:3.

[0047] Example 6

[0048] The only difference between this embodiment and embodiment 1 is that the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 7:4.

[0049] Example 7

[0050] The only difference between this embodiment and embodiment 1 is that the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 7:5.

[0051] Example 8

[0052] The only difference between this embodiment and embodiment 6 is that 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is replaced by an equal amount of tris(vinyldimethylsilyloxy)methylsilane.

[0053] Example 9

[0054] The only difference between this embodiment and embodiment 6 is that 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is replaced by an equal amount of 1,3-bis(3-carboxypropyl)tetramethyldisilane.

[0055] Example 10

[0056] The only difference between this embodiment and embodiment 9 is that the maleic anhydride grafted polypropylene is replaced by equal amounts of maleic anhydride grafted polypropylene and polyethyleneimine in a mass ratio of 6:1.

[0057] Embodiment 11

[0058] The only difference between this embodiment and Embodiment 10 is that the mass ratio of maleic anhydride grafted polypropylene to polyethyleneimine is 1:1.

[0059] Example 12

[0060] The only difference between this embodiment and embodiment 10 is that the mass ratio of maleic anhydride grafted polypropylene to polyethyleneimine is 5:1.

[0061] Example 13

[0062] The only difference between this embodiment and embodiment 10 is that the mass ratio of maleic anhydride grafted polypropylene to polyethyleneimine is 5:3.

[0063] Comparative Example 1

[0064] The only difference between this comparative example and Example 1 is that the modified basalt fiber is replaced by an equal amount of basalt fiber.

[0065] Comparative Example 2

[0066] The only difference between this comparative example and Example 1 is that isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is replaced by an equal amount of 2,2-bis[(4-trimethylsilyloxy)phenyl]propane.

[0067] Comparative Example 3

[0068] The only difference between this comparative example and Example 1 is that 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is replaced by an equal amount of isopropyl tri(dioctyl pyrophosphate) titanate.

[0069] The plastic anchor bolts prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were combined with a disc-shaped plastic expansion tube and a steel nail to obtain a plastic anchor bolt. The standard value of the tensile bearing capacity of the anchor bolt at a minimum ambient temperature of 0° C. was tested according to the test method in JG / T 366-2012 “Anchor bolts for exterior wall insulation”; the test results are shown in Table 1.

[0070] Table 1 Test results of plastic anchor performance

[0071]

[0072] Compared with Comparative Examples 1 to 3, in Example 1, isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane were used to modify the basalt fiber. As a result, the standard value of the tensile bearing capacity of the plastic anchor prepared in Example 1 at 0°C was higher than that of Comparative Examples 1 to 3, indicating that the use of titanate coupling agent and silicon-oxygen-containing compounds to modify the basalt fiber can improve the low temperature resistance of the plastic anchor.

[0073] Compared with Example 1, Examples 4 to 7 change the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane. As a result, the standard values ​​of the tensile bearing capacity of the plastic anchors prepared in Examples 5 to 7 at 0°C are higher than those in Example 1 and Example 4, indicating that when the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 7:3 to 5, the low temperature resistance of the plastic anchor can be further improved; by comparing Examples 5 to 7, it is found that the standard value of the tensile bearing capacity of the plastic anchor prepared in Example 6 at 0°C is higher than that in Example 5 and Example 7, indicating that when the mass ratio of isopropyl tri(dioctyl pyrophosphate) titanate and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane is 7:4, the obtained plastic anchor has high low temperature resistance.

[0074] Compared with Example 6, Examples 8 and 9 use different silicon-oxygen-containing compounds. As a result, the standard value of the tensile bearing capacity of the plastic anchor prepared in Example 9 at 0°C is higher than that of Examples 6 and 8, indicating that when the silicon-oxygen-containing compound is 1,3-bis(3-carboxypropyl)tetramethyldisilane, the low-temperature resistance of the plastic anchor can be further improved.

[0075] Compared with Example 9, the compatibilizer in Examples 10 to 13 consists of maleic anhydride grafted polypropylene and polyethyleneimine. As a result, the standard value of the tensile bearing capacity of the plastic anchor bolts prepared in Examples 10 to 13 at 0°C is higher than that in Example 9, indicating that when the compatibilizer consists of maleic anhydride grafted polypropylene and polyethyleneimine, the low temperature resistance of the plastic anchor bolt can be further improved; by comparing Examples 10 to 13, it is found that the standard value of the tensile bearing capacity of the plastic anchor bolts prepared in Examples 12 to 13 at 0°C is higher than that in Examples 10 to 11, indicating that when the mass ratio of maleic anhydride grafted polypropylene to polyethyleneimine is 5:1 to 3, the low temperature resistance of the plastic anchor bolt can be further improved.

[0076] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength plastic material for anchor bolts, characterized in that: The raw materials include the following components in parts by weight: 50-60 parts of polyamide resin, 30-40 parts of polypropylene, 10-20 parts of modified basalt fiber, 0.6-1 part of compatibilizer, and 1-2 parts of lubricant, wherein the modified basalt fiber is obtained by modifying basalt fiber with a modifier, and the modifier includes a titanate coupling agent and a silicon-oxygen-containing compound; The mass ratio of the titanate coupling agent to the silicon-oxygen-containing compound is 7:3-5; The silicon-oxygen-containing compound includes one or more of 1,3-bis(3-carboxypropyl)tetramethyldisilane, tri(vinyldimethylsilyloxy)methylsilane, and 2,2-bis[(4-trimethylsilyloxy)phenyl]propane.

2. The high-strength plastic material for anchor bolts according to claim 1, characterized in that: The amount of the modifier added is 1% to 3% of the mass of the basalt fiber.

3. The high-strength plastic material for anchor bolts according to claim 1, characterized in that: The titanate coupling agent includes one or both of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropyl tri(isostearoyl) titanate.

4. The high-strength plastic material for anchor bolts according to claim 1, characterized in that: The silicon-oxygen-containing compound is 1,3-bis(3-carboxypropyl)tetramethyldisilane.

5. The high-strength plastic material for anchor bolts according to claim 1, characterized in that: The preparation method of the modified basalt fiber comprises the following steps: The basalt fiber is added into a solvent, a modifier is added for modification, and the modified basalt fiber is obtained after drying.

6. The high-strength plastic material for anchor bolts according to claim 1, characterized in that: The compatibilizer includes one or two of maleic anhydride grafted polypropylene and polyethyleneimine.

7. The high-strength plastic material for anchor bolts according to claim 6, characterized in that: When the compatibilizer includes maleic anhydride grafted polypropylene and polyethyleneimine, the mass ratio of the maleic anhydride grafted polypropylene to the polyethyleneimine is 5:1-3.

8. A plastic anchor bolt, characterized in that: It comprises a screw and a plastic expansion tube with a disc, wherein the material of the plastic expansion tube with a disc is the high-strength plastic material for anchor bolts as claimed in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyphthalamide composite material and preparation method thereof

    CN102250467A